Promoting freedom learning implementation through self-determined learning: A study of students perspectives - Kartika Isna Sujati; Amir Syamsudin; Delyanti Azzumarito Pulungan; Ernita Apriani; Nimas Putri Dewi Puspitaningrum (Universitas Negeri Yogyakarta, 2023)
This study is aimed to describe the students' perspective towards self-determined learning to promote freedom learning implementation. The survey research design with clustered sampling technique was used to collect 380 senior high school students' responses. The questionnaire that was used in the survey have validated using Pearson Product Moment and reliably known by the Alpha-Cronbach score. Descriptive statistics used as the data analytical technique to describe the senior high students' perspective towards self-determined learning to promote the freedom learning implementation. The results showed that freedom learning fundamental points have similar points with self-determined learning principles consisting of heutagogy and autonomous learning skills. The main conclusion concludes that the students' perspective toward self-determined learning could promote freedom learning implementation. The study's recommendations are be expanded the cluster sampling and be emerged the survey in the case during and after the Covid-19 pandemic the that is indirectly fostering the students' heutagogy and autonomous skill by emphasizing self-determined learning.